LOCALIZATION OF AXIAL AND RADIAL DISPLACEMENT IN AIR-CORE TRANSFORMER USING FREQUENCY RESPONSE ANALYSIS - Sarbupin, Temirlan (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The axial and radial displacement of transformer windings can lead to significant defects, accounting for a large proportion of transformer failures. These defects not only result in power outages but also pose serious safety risks. This paper presents a novel methodology for the localization of axial and radial displacement in air-core transformers. Utilizing Frequency Response Analysis (FRA) coupled with deterministic algorithms. The proposed approach involves analytical modelling of the transformer, data collection through software simulation, and measurements. By creating a comprehensive lookup table for potential winding displacements, this method leverages software simulations in Python and SPICE to accurately predict and identify the location winding deformations. The deterministic algorithm is implemented as a key factor in the reliable prediction of such displacements.
Keywords: Type of access: Open Access; Axial deformation; radial deformation; displacement; frequency response analysis